1942
DOI: 10.5962/bhl.title.7268
|View full text |Cite
|
Sign up to set email alerts
|

Catalogue of bacteria associated extracellularly with insects and ticks, by Edward A. Steinhaus...

Abstract: Streptococceae 136 Genus : Diplococcus 136 Genus : Streptococcus 158 58353 iii CATALOGUE OF BACTERIA ASSOCIATED EXIRACELLULARLY WITH INSECTS AND TICKS Lygaeidae which, she says, undoubtedly carry "bacteria in their cecal appendages. She found the ceca to "be as well filled with "bacteria after the long period of winter rest as they were during the active summer season. Kuskop "believes the "bacteria play a symbiotic role in "being essential in the physiology of the insect's digestion. Fate of Bacteria During M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1945
1945
1975
1975

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The number of insect and arthropod hosts and vectors is large. Steinhaus (1942) lists 52 insects and arthropods associated in some manner with this organism. Three ticks are good biologic hosts, transmitting the organism via their eggs, larvae, and numphs to adults of the next generation.…”
Section: Discussionmentioning
confidence: 99%
“…The number of insect and arthropod hosts and vectors is large. Steinhaus (1942) lists 52 insects and arthropods associated in some manner with this organism. Three ticks are good biologic hosts, transmitting the organism via their eggs, larvae, and numphs to adults of the next generation.…”
Section: Discussionmentioning
confidence: 99%
“…One of the commonly held generalizations is that blood feeding arthropods have sterile intestines, or, if they become contaminated while feeding, they are able to rid themselves of bacteria (Steinhaus, 1942;Weyer, 1960 insects as grasshoppers which are sterile upon hatching, but soon acquire a bacterial flora which increases both in absolute numbers and in variety of species as the insect develops (Bucher, 1960).…”
Section: Discussionmentioning
confidence: 99%
“…Having exhausted all of the prospective sources of this contaminant through a thorough study of all materials utilized in the manufacture of the sirup used, in all the plants in which it was produced, the idea occurred to us that possibly this Tomla species was transmitted by some insect carrier. This was suggested by the very extensive work of Steinhaus (1941), whose study of the bacteria associated with many species of insects has given great emphasis to the source of this contamination. I n his classic contribution to this subject he showed that from the 30 species of insects studied he isolated 83 strains of bacteria.…”
Section: Characteristic Alcoholic Fermentation Induced By Torula Acidmentioning
confidence: 99%